2006 Information and Communications for Development : Global Trends and Policies - World Bank (Washington, DC: World Bank, 2012)
The book offers a realistic assessment of experiences, trends, and outlook on the Information, Communications Technology (ICT) sector, with a focus on actual results and justified expectations. It attempts to track and analyze global ICT development trends, and to provide empirical evidence of the benefits that ICT is providing in terms of economic growth and poverty reduction. Indicators for the Millennium development Goals (MDG) targets, among others, have been incorporated into the ICT At-a-Glance tables compiled for this report. It contributes to the creation of a basis for more systematic monitoring and evaluation (M&E) of the progress and impact of ICT, and provides as well as useful insights on ICT for development in general. Besides consolidating all these M&E efforts and sharing of the findings with the development community, the report also includes analytical work that applies these data to a range of topics: investment trends, principles and practical solutions to extending ICT services, the role of ICT in doing business, trends in national e-strategies, and approaches to tracking ICT globally. Part I of the report assesses topics essential to developing ICT. It contains chapters on investment (chapter 2), access (chapter 3), diffusion and use (chapter 4), country policies and strategies (chapter 5), and targets, monitoring, and evaluation (chapter 6). Each chapter provides a theoretical and qualitative framework supported by quantitative evidence. Where limited data impede comprehensive economic analysis, a case study approach is used. Part II presents the new Bank ICT At-a-Glance tables for 144 economies, which show the most recent national data on key indicators of ICT development, including access, quality, affordability, efficiency, sustainability, and applications.